Projecting Presence: Creating an "Effet de Présence" for Virtual Characters - Ahluwalia, Kyle (Université d'Ottawa / University of Ottawa, 2014)
Given the expansion of multimedia technology and proliferation of moving projections on the theatre stage in the 21st century, this thesis examines how a virtual or projected character can appear to be present without a physical body on the stage. This study is grounded in the theories of effet de présence (effect of presence) as elaborated by Josette Féral, but also uses other theories to look at how productions can create such an effect for virtual characters. Specifically, this thesis examines the character’s relationship with the real, framing devices and actions of the characters. The specific examples of Rwanda 94 (Groupov), La Belle et la Bête (4D Art) and Les Aveugles (UBU CC) are used as case studies in order to focus on these techniques. Partant de l’intégration des nouvelles technologies et la prolifération des projections vidéo au sein des scènes théâtrales du 21e siècle, cette thèse examine les techniques par lesquel les personnages projeté peut sembler présent en l’absence d’un corps physique visible. Cette réflexion est basée sur l’effet de présence, concept élaboré par Josette Féral, ainsi que d’autres théories et examine comment un effet de présence est constitué pour ces personnages virtuels en considérant leur relation au réel (mimesis), les dispositifs de cadrage dans lesquels ils s’inscrivent de même que leurs actions. Cette analyse sera menée à porter de avec trois étudies de cas : Rwanda 94 (Groupov), La Belle et la Bête (4D Art) et Les Aveugles (UBU CC).
Keywords: Contemporary Theatre; Presence; Effet de presence (effect of presence); Framing; Projections; Virtual Characters; Multimedia Theatre; Mimesis